The Use of Prophetic Communication and Religious Message as a Way to Prevent COVID-19 Outbreak in Palu City - Muhammad Khairil; Raisa Alatas; Dyah Fitria Kartika Sari (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2021)
This study discusses prophetic communication in spreading religious messages for the Coronavirus (COVID-19) outbreak prevention in Palu, Indonesia. This study is based on qualitative research with a case study approach. This study will lead to a detailed and in-depth description of the problem regarding the condition according to what happened in the field. The case study conducted in this research took place in Alkhairaat Foundation of Palu, Central Sulawesi. To support existing data, researchers also made direct observations to the Alkhairaat Foundation. Religion is not only a guide but also a source of life. The function of religion is to regulate human life such as amidst the COVID-19 outbreak through the basis of the Qur'an and hadith. Qur'an and Hadith become the basis in the formation of religious messages that are assembled by the Ulamas through their social media. Public opinion is then filled with tendencies that lead to Islamic ideas and at the same time, there are rejections of it which portray acceptance of information to have positive and negative sides. Ulamas used social media such as Facebook, WhatsApp, and online news. Ulamas also coordinate with local government to unite the perceptions on how to face the COVID-19 that also happened in Palu. Ulamas perform their roles by conveying fatwas. The strong influence of an Ulama as a figure means that every word and deed can be a hold for the people. In this case, Ulamas should remain consistent with what was conveyed. Because the conveyed fatwa is not an individual fatwa but an institutionalized fatwa